KARAKTERISTIK LEVEL METAKOGNISI SISWA SD DALAM MENYELESAIKAN MASALAH MATEMATIKA - Theresia Laurens, (Jurnal Penelitian Pendidikan Matematika dan Sains, 2008)
Abstract: The goal of teaching problem solving in mathematics is to develop students ability in monitoring and evaluating their  owns thinking process. Such ability represent the part of mental activity which called metacognition. The process of problem solving happened by interaction among cognition and metacognition activity, where this interaction can be shown in a level of awareness is called by the level  of metacognition. By analysing the characteristic of students metacognition when they solved  mathematics problem, and compare it with the indicators of every metacognitions level, then empirical we can find the characteristics  of the metacognitions level.